Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.3389/fmicb.2018.01577
|View full text |Cite
|
Sign up to set email alerts
|

Related Endogenous Retrovirus-K Elements Harbor Distinct Protease Active Site Motifs

Abstract: Background: Endogenous retrovirus-K is a group of related genomic elements descending from retroviral infections in human ancestors. HML2 is the clade of these viruses which contains the most intact provirus copies. These elements can be transcribed and translated in healthy and diseased tissues, and some of them produce active retroviral enzymes, such as protease. Retroviral gene products, including protease, contribute to illness in exogenous retroviral infections. There are ongoing efforts to test anti-retr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 97 publications
0
11
0
Order By: Relevance
“…Four ORFs were observed over the 7,455 bp genome and assigned as the gag, pro, pol and env genes based on the presence of conserved domains. In the pro gene we were able to identify an active site motif DTGAD predominately observed in functional retroviruses, and a helix motif GRDVL (Turnbull and Douville, 2018). We were unable to identify complete long terminal repeat (LTR) regions in the 7,455 bp genome, although this may be due to incomplete assembly at the 5’ and/or 3’ end, rather than a true absence of LTRs.…”
Section: Resultsmentioning
confidence: 99%
“…Four ORFs were observed over the 7,455 bp genome and assigned as the gag, pro, pol and env genes based on the presence of conserved domains. In the pro gene we were able to identify an active site motif DTGAD predominately observed in functional retroviruses, and a helix motif GRDVL (Turnbull and Douville, 2018). We were unable to identify complete long terminal repeat (LTR) regions in the 7,455 bp genome, although this may be due to incomplete assembly at the 5’ and/or 3’ end, rather than a true absence of LTRs.…”
Section: Resultsmentioning
confidence: 99%
“…In general, pro-encoded proteins have two domains, a pseudoprotease (protease-like) domain that has deoxyuridine triphosphatase (dUTPase) activity and an active protease (PR) [28,29]. We found that the CERV β1 pro contains a dUTPase domain at its 5′ end (Figure 1), and the protease activity was confirmed since this sequence bears the core amino acid sequence of a retroviral aspartyl protease Leu-Asp-Thr-Gly (nt 2536-2547) [28,30]. Interestingly, such as other betaretroviruses [6], CERV β1 pro encodes a glycine-rich region called the G-patch domain [31].…”
Section: Identification Of Betaretrovirus In Australian Deer Genomementioning
confidence: 86%
“…Ethically-sourced human autopsy tissues were obtained from the NIH Neurobiobank and the Veterans Affairs Brain Bank. Cell culture, transfections, cytokine treatments, western blot, chromatin immunoprecipitation, quantitative PCR, immunohistochemistry/histological staining, RNAseq analysis, and computational biology were done as described previously [7,8,[47][48][49]. Detailed descriptions of the methodologies are provided in Supplementary Methods.…”
Section: Methodsmentioning
confidence: 99%